Development of clusters in the spacerocket industry as the instrument of forming of the innovation economy - Nezhnikova, E.V.; Glyuzitskiy, K.K. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Ėkonomika, 2018)
The paper studies state of development of the space-rocket industry of Russia in the conditions of application of cluster approach is characterized. The author analyzes benefits of transition to the innovation economy by an industry clustering, benefits and shortcomings of cluster policy in detail are considered, the most perspective clusters in the space-rocket industry come to light, comparative analysis of clusters on key performance indicators is carried out. On the basis of the carriedout analysis the author provides the set of guidelines for increase in efficiency of functioning of the existing industry clusters, special attention is focused on increase in number of the participating companies, production process differentiation strengthening and also importance of increase in research potential of the industry is noted.